Diction in Liverpool vs Manchester United Football Commentary, March 2023 - Ardiansyah, Rafli; Djuharie, Otong Setiawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research investigates the wording and figurative language used by Peter Drury during the Liverpool vs Manchester United match on March 5, 2023, which ended in a 7–0 victory for Liverpool. The study aims to analyze how the selection of words, metaphors, hyperbole, and rhetorical devices shape the emotional intensity and dramatic narrative of the match. Using a qualitative descriptive approach, the research focuses on commentary utterances selected from the match transcript, highlighting evaluative language and stylistic patterns. Findings reveal that Drury’s wording evolves from neutral description to expressive exaggeration in line with the unfolding scoreline. Metaphors such as “A Kop explosion” and “red utopia,” evaluative phrases like “formidable” and “day of his life,” and rhetorical questions contribute to constructing a sense of dominance, unpredictability, and historical significance. The commentator’s stylistic choices amplify excitement, convey the atmosphere, and transform the match into a performative spectacle for viewers. The study underscores the role of sports commentary as a performative discourse, showing that linguistic creativity in live commentary not only informs but also emotionally engages the audience, enhancing the overall football viewing experience.